High-performance fiber containing carbon nanotubes and preparation method thereof
By introducing carbon nanotubes and double-layer coated ammonium polyphosphate materials into high-performance fibers, and using electrostatic layer self-assembly technology of aminolated and antibacterial layers, the problem of fibers being prone to bacterial growth and insufficient flame retardant performance in moisture or body fluids is solved, achieving efficient flame retardant and antibacterial improvement.
Patent Information
- Application Number
- CN202411824267.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-25
AI Technical Summary
Existing high-performance fibers are prone to breed bacteria when exposed to moisture or body fluids, and have insufficient flame retardant performance, making it difficult to meet the needs of medical, sports, aerospace and other fields.
By introducing carbon nanotubes and double-layer coated ammonium polyphosphate material into the fibers, and preparing fibers through melt spinning technology, combining electrostatic layer self-assembly technology with aminolation and antibacterial layers, the flame retardancy and antibacterial properties of the fibers are improved.
It achieves good flame retardant and antibacterial properties of high-performance fibers, can reduce bacterial growth when exposed to moisture or body fluids, and improve the safety and breadth of fibers.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-performance fibers, in particular to a high-performance fiber containing carbon nanotubes and a preparation method thereof. Background Art
[0002] High-performance fibers play a vital role in modern society. Their modern value is reflected in many key areas, significantly improving the level of technology and application effects. With their excellent physical properties, durability and adaptability, these fibers have promoted technological progress and innovative applications in fields ranging from aerospace to medical, construction to sports equipment. First, in the field of aerospace, the use of high-performance fibers is crucial. These fibers usually have extremely high tensile strength and heat resistance, and can effectively withstand extreme environmental conditions. In aerospace devices, the use of high-performance fibers such as carbon fiber composites can significantly reduce the weight of the structure and improve flight efficiency and safety. For example, in the structural components of space shuttles and satellites, the use of high-performance fiber materials can reduce the overall weight while improving the ability to withstand high temperatures and impacts, thereby enhancing the reliability and performance of the aircraft. In the medical field, the application of high-performance fibers is also extensive. Medical devices such as surgical textiles, implants and stents can use these fibers to enhance their mechanical properties and biocompatibility. For example, high-performance fiber stents in the biomedical field can support tissue regeneration, promote wound healing, and improve patient recovery. Its excellent mechanical properties and stability enable these medical devices to maintain good function during long-term use. In the construction sector, high-performance fibers are used to reinforce concrete and other building materials, which can improve the strength and durability of buildings. The use of such materials can reduce the frequency and cost of maintenance of buildings, increase their service life, and provide better structural stability in earthquakes and other extreme conditions.
[0003] However, in many application scenarios, fiber materials will come into contact with moisture or body fluids, and these environments are prone to breeding bacteria. Especially in the medical and sports fields, medical textiles such as surgical gowns, bed sheets and wound dressings need to have excellent antibacterial properties to reduce the risk of infection and improve the patient's recovery effect. Secondly, the improvement of flame retardant properties is also a characteristic of high-performance fibers that cannot be ignored. In firefighter uniforms, military equipment and aerospace fields, flame retardant properties are a basic requirement to ensure personnel safety. Therefore, it is very necessary to improve the flame retardant properties of fiber materials to meet the flame retardant needs in specific fields.
[0004] In order to overcome the defects of the prior art, the present invention provides a high-performance fiber containing carbon nanotubes and a preparation method thereof. Summary of the invention
[0005] The object of the present invention is to provide a high-performance fiber containing carbon nanotubes and a preparation method thereof, so as to solve the problems in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A method for preparing high-performance fibers containing carbon nanotubes comprises the following steps:
[0008] Step 1: heating the solvent to 45-50°C, adding ammonium polyphosphate and alkylphenol polyoxyethylene ether and adjusting the pH to 9-10, stirring evenly, and then slowly adding tetraethyl orthosilicate, stirring and reacting at 45-50°C for 4-5h, cooling, filtering, washing and drying after the reaction is completed to prepare a silicon-coated ammonium polyphosphate material; mixing the silicon-coated ammonium polyphosphate material and anhydrous ethanol, stirring for 30-40min, and then heating to 60-70°C and adding γ-aminopropyl triethoxysilane dropwise, continuing to stir for 30-40min, cooling, filtering, washing and drying after the reaction is completed to prepare a modified silicon-coated ammonium polyphosphate material;
[0009] Step 2: adding tris(hydroxymethyl)aminomethane hydrochloride to obtain a buffer solution with a pH of 8.3-8.5; adding tannic acid and modified silicon-coated ammonium polyphosphate material to the buffer solution, stirring at 25-30° C. for 5-7 hours, filtering, washing and drying after the reaction to obtain a double-layer coated ammonium polyphosphate material; mixing the carbon nanotube material, the double-layer coated ammonium polyphosphate material and poly(trimethylene terephthalate), and obtaining a masterbatch by melt granulation; mixing the masterbatch, compatibilizer ABS-g-MAH and polypropylene, and obtaining fibers by melt spinning;
[0010] Step 3: Immerse the fiber in ethylenediamine solution, stir and react for 60-80 minutes to obtain amino fiber; immerse the amino fiber in polyglutamic acid solution, stir and react for 30-40 minutes, wash with deionized water after the reaction, immerse in chitosan solution, stir and react for 30-40 minutes, wash with acetic acid solution after the reaction; repeat the above steps for the amino fiber 3 times to obtain high-performance fiber.
[0011] More optimally, in step 1, the solvent is composed of anhydrous ethanol and deionized water in a volume ratio of 3:
[0012] (1.0-1.5).
[0013] More optimally, in step one, the reaction mass ratio of ammonium polyphosphate, alkylphenol polyoxyethylene ether, tetraethyl orthosilicate and γ-aminopropyltriethoxysilane is 10:0.1:(2.0-2.5):1.
[0014] More optimally, in step 2, the reaction mass ratio of tannic acid and modified silicon-coated ammonium polyphosphate material is 1:(1.0-1.2).
[0015] More optimally, in step 2, the contents of the fiber components are: by mass fraction, 2-5% carbon nanotube material, 5-8% double-layer coated ammonium polyphosphate material, 30-36% polytrimethylene terephthalate, 2-5% compatibilizer ABS-g-MAH, and the remainder is polypropylene.
[0016] More optimally, in step 2, the melt granulation parameters are: temperature of 200-250°C, and rotation speed of 120-140rpm.
[0017] More optimally, in step 2, the melt spinning parameters are: temperature of 250-300°C, winding speed of 1000-1200m / min.
[0018] More optimally, in step three, the stirring reaction temperature is 25-30°C.
[0019] More optimally, in step three, ethylenediamine is dissolved in methanol to obtain a 40-50wt% ethylenediamine solution; polyglutamic acid is dissolved in deionized water to obtain a 3-5g / mL polyglutamic acid solution; and chitosan is dissolved in acetic acid solution to obtain a 1-2g / mL chitosan solution.
[0020] Beneficial effects of the present invention:
[0021] The present invention is characterized in that, in step 1, by adding ammonium polyphosphate, alkylphenol polyoxyethylene ether and tetraethyl orthosilicate, a silicon-coated ammonium polyphosphate material is obtained; in this step, by adding alkylphenol polyoxyethylene ether as a surfactant, tetraethyl orthosilicate undergoes a hydrolysis condensation reaction under alkaline conditions and forms a silicon coating layer on the surface of ammonium polyphosphate, and the silicon coating layer can effectively isolate and protect ammonium polyphosphate, thereby improving its stability and flame retardant performance. Then, by adding the silicon-coated ammonium polyphosphate material, γ-aminopropyl triethoxysilane and anhydrous ethanol, a modified silicon-coated ammonium polyphosphate material is obtained, and the purpose of this step is to introduce the active group amino group into the surface of the silicon-coated ammonium polyphosphate material.
[0022] The present invention is characterized in that, in step 2, a modified silicon-coated ammonium polyphosphate material, tannic acid and a buffer solution are mixed to obtain a double-layer coated ammonium polyphosphate material; and a carbon nanotube material, a double-layer coated ammonium polyphosphate material, poly(trimethylene terephthalate), a compatibilizer ABS-g-MAH and polypropylene are added to obtain fibers through melt spinning. In this step, the modified silicon-coated ammonium polyphosphate material containing an active amino group and the tannic acid containing pyrogallol undergo a Schiff base reaction or a Michael addition reaction to obtain a dopamine-like layer, and finally prepare a double-layer coated ammonium polyphosphate material. The core layer of the double-layer coated ammonium polyphosphate material and the first silicon coating layer have good flame retardant effects. The active groups such as phenolic hydroxyl and amino groups in the outermost dopamine-like layer of the double-layer coated ammonium polyphosphate material can form hydrogen bonds or other non-covalent interactions with other components in the fiber (such as carbon nanotubes, poly(trimethylene terephthalate), compatibilizer ABS-g-MAH and polypropylene), thereby improving the compatibility between these components; in addition, since the dopamine-like layer has strong adhesion, it can reduce the interfacial tension between different materials and form a good interface between the different components of the fiber.
[0023] The feature of the present invention is that in step three, the fiber is sequentially immersed in an ethylenediamine solution, a polyglutamic acid solution, and a chitosan solution to obtain a high-performance fiber. In this step, the polytrimethylene terephthalate component of the high-performance fiber and ethylenediamine can undergo an aminolysis reaction to introduce an amino group (an amino group is a positively charged group) on the fiber surface, and then the polyglutamic acid antibacterial layer is introduced by immersing a polyglutamic acid solution (containing a negative charge), and then the chitosan antibacterial layer is introduced by immersing a chitosan solution (containing a positive charge), that is, by electrostatic attraction layer by layer self-assembly, a high-performance fiber with good antibacterial properties is prepared. In summary, the high-performance fiber obtained by the present invention has good flame retardancy and antibacterial properties, and therefore has broad application prospects in the field of high-performance fiber technology. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Source of raw materials:
[0026] Ammonium polyphosphate, provided by Shandong Hui'an Chemical Co., Ltd., with a particle size of 200 mesh and an effective ingredient content of 99%; carbon nanotube material, provided by Dongguan Changsheng Plastic Raw Materials Co., Ltd., model PPOCS-A156TG; polytrimethylene terephthalate, provided by Dongguan Yingxiang Plastic Raw Materials Co., Ltd., with a density of 1.3g / cm3 ; Polypropylene, provided by Shanghai Shunshi Plastics Co., Ltd., model Y16; compatibilizer ABS-g-MAH, provided by Guangdong Chuanheng New Materials Technology Co., Ltd., model CH-906; polyglutamic acid, provided by Guangdong Hongyou Biotechnology Co., Ltd., model food grade; chitosan, provided by Guangdong Mingcheng Biotechnology Co., Ltd., molecular weight 161.16, active ingredient content 99%.
[0027] Embodiment 1: Step 1: Heat the solvent to 50°C, add ammonium polyphosphate and alkylphenol polyoxyethylene ether and adjust the pH to 10, stir evenly and then slowly add tetraethyl orthosilicate, stir and react at 50°C for 5h, cool, filter, wash and dry after the reaction to prepare a silicon-coated ammonium polyphosphate material; mix the silicon-coated ammonium polyphosphate material and anhydrous ethanol, stir well for 40min, heat to 70°C and add γ-aminopropyl triethoxysilane dropwise, continue stirring for 40min, cool, filter, wash and dry after the reaction to prepare a modified silicon-coated ammonium polyphosphate material; wherein the solvent is composed of anhydrous ethanol and deionized water in a volume ratio of 3:1; the reaction mass ratio of ammonium polyphosphate, alkylphenol polyoxyethylene ether, tetraethyl orthosilicate and γ-aminopropyl triethoxysilane is 10:0.1:2.5:1;
[0028] Step 2: adding tris(hydroxymethyl)aminomethane hydrochloride to obtain a buffer solution with a pH of 8.5; adding tannic acid and modified silicon-coated ammonium polyphosphate material to the buffer solution, stirring at 30° C. for 7 hours, and after the reaction is completed, filtering, washing, and drying to obtain a double-layer coated ammonium polyphosphate material; the reaction mass ratio of tannic acid to modified silicon-coated ammonium polyphosphate material is 1:1.2;
[0029] Step 3: By mass fraction, 2% carbon nanotube material, 5% double-layer coated ammonium polyphosphate material and 35% polytrimethylene terephthalate are mixed, and master batches are obtained by melt granulation; the master batch, 2% compatibilizer ABS-g-MAH and 56% polypropylene are mixed, and fibers are obtained by melt spinning; melt granulation parameters: temperature is 250°C, rotation speed is 140rpm; melt spinning parameters: temperature is 300°C, winding speed is 1200m / min;
[0030] Step 4: dissolving ethylenediamine in methanol to obtain a 50 wt% ethylenediamine solution; dissolving polyglutamic acid in deionized water to obtain a 5 g / mL polyglutamic acid solution; dissolving chitosan in acetic acid solution to obtain a 2 g / mL chitosan solution;
[0031] The fiber was immersed in a 50wt% ethylenediamine solution, stirred and reacted at 30°C for 80 minutes to obtain an amino fiber; the amino fiber was immersed in a polyglutamic acid solution, stirred and reacted at 30°C for 40 minutes, washed with deionized water after the reaction, and then immersed in a chitosan solution, stirred and reacted at 30°C for 40 minutes, and washed with acetic acid solution after the reaction; the above steps were repeated for the amino fiber 3 times to obtain a high-performance fiber.
[0032] Example 2: Step 1: Heat the solvent to 47°C, add ammonium polyphosphate and alkylphenol polyoxyethylene ether and adjust the pH to 9.5, stir evenly, then slowly add tetraethyl orthosilicate, stir and react at 47°C for 4.5h, cool, filter, wash and dry after the reaction to prepare a silicon-coated ammonium polyphosphate material; mix the silicon-coated ammonium polyphosphate material and anhydrous ethanol, stir well for 35min, heat to 65°C and add γ-aminopropyl triethoxysilane dropwise, continue stirring for 35min, cool, filter, wash and dry after the reaction to prepare a modified silicon-coated ammonium polyphosphate material; wherein the solvent is composed of anhydrous ethanol and deionized water in a volume ratio of 3:1; the reaction mass ratio of ammonium polyphosphate, alkylphenol polyoxyethylene ether, tetraethyl orthosilicate and γ-aminopropyl triethoxysilane is 10:0.1:2.5:1;
[0033] Step 2: by adding tris(hydroxymethyl)aminomethane hydrochloride, a buffer solution with a pH of 8.4 is obtained; tannic acid and modified silicon-coated ammonium polyphosphate material are added to the buffer solution, and stirred at 27°C for 6 hours. After the reaction is completed, the double-layer coated ammonium polyphosphate material is obtained by suction filtration, washing, and drying; the reaction mass ratio of tannic acid to modified silicon-coated ammonium polyphosphate material is 1:1.2;
[0034] Step 3: By mass fraction, 2% carbon nanotube material, 5% double-layer coated ammonium polyphosphate material and 35% polytrimethylene terephthalate are mixed, and master batches are obtained by melt granulation; the master batch, 2% compatibilizer ABS-g-MAH and 56% polypropylene are mixed, and fibers are obtained by melt spinning; melt granulation parameters: temperature is 225°C, rotation speed is 130rpm; melt spinning parameters: temperature is 270°C, winding speed is 1100m / min;
[0035] Step 4: dissolving ethylenediamine in methanol to obtain a 45 wt% ethylenediamine solution; dissolving polyglutamic acid in deionized water to obtain a 4 g / mL polyglutamic acid solution; dissolving chitosan in acetic acid solution to obtain a 1.5 g / mL chitosan solution;
[0036] The fiber was immersed in a 45wt% ethylenediamine solution, stirred and reacted at 27°C for 70 minutes to obtain an amino fiber; the amino fiber was immersed in a polyglutamic acid solution, stirred and reacted at 27°C for 35 minutes, washed with deionized water after the reaction, and then immersed in a chitosan solution, stirred and reacted at 27°C for 35 minutes, and washed with acetic acid solution after the reaction; the above steps were repeated for the amino fiber 3 times to obtain a high-performance fiber.
[0037] Example 3: Step 1: Heat the solvent to 45°C, add ammonium polyphosphate and alkylphenol polyoxyethylene ether and adjust the pH to 9, stir evenly, then slowly add tetraethyl orthosilicate, stir and react at 45°C for 4h, cool, filter, wash and dry after the reaction to prepare a silicon-coated ammonium polyphosphate material; mix the silicon-coated ammonium polyphosphate material and anhydrous ethanol, stir well for 30min, heat to 60°C and add γ-aminopropyl triethoxysilane dropwise, continue stirring for 30min, cool, filter, wash and dry after the reaction to prepare a modified silicon-coated ammonium polyphosphate material; wherein the solvent is composed of anhydrous ethanol and deionized water in a volume ratio of 3:1; the reaction mass ratio of ammonium polyphosphate, alkylphenol polyoxyethylene ether, tetraethyl orthosilicate and γ-aminopropyl triethoxysilane is 10:0.1:2.5:1;
[0038] Step 2: adding tris(hydroxymethyl)aminomethane hydrochloride to obtain a buffer solution with a pH of 8.3; adding tannic acid and modified silicon-coated ammonium polyphosphate material to the buffer solution, stirring at 25°C for 5 hours, and filtering, washing, and drying after the reaction to obtain a double-layer coated ammonium polyphosphate material; the reaction mass ratio of tannic acid to modified silicon-coated ammonium polyphosphate material is 1:1.2;
[0039] Step 3: By mass fraction, 2% carbon nanotube material, 5% double-layer coated ammonium polyphosphate material and 35% polytrimethylene terephthalate are mixed, and master batches are obtained by melt granulation; the master batch, 2% compatibilizer ABS-g-MAH and 56% polypropylene are mixed, and fibers are obtained by melt spinning; melt granulation parameters: temperature is 200°C, rotation speed is 120rpm; melt spinning parameters: temperature is 250°C, winding speed is 1000m / min;
[0040] Step 4: dissolving ethylenediamine in methanol to obtain a 40 wt% ethylenediamine solution; dissolving polyglutamic acid in deionized water to obtain a 3 g / mL polyglutamic acid solution; dissolving chitosan in acetic acid solution to obtain a 1 g / mL chitosan solution;
[0041] The fiber was immersed in a 40wt% ethylenediamine solution, stirred and reacted at 25°C for 60 minutes to obtain an amino fiber; the amino fiber was immersed in a polyglutamic acid solution, stirred and reacted at 25°C for 30 minutes, washed with deionized water after the reaction, and then immersed in a chitosan solution, stirred and reacted at 25°C for 30 minutes, and washed with acetic acid solution after the reaction; the above steps were repeated 3 times for the amino fiber to obtain a high-performance fiber.
[0042] Comparative Example 1: The double-layer coated ammonium polyphosphate material is replaced with ammonium polyphosphate provided by Shandong Hui'an Chemical Co., Ltd., and the rest is the same as Example 1, and the specific steps are as follows: Step 1: By mass fraction, 2% carbon nanotube material, 5% ammonium polyphosphate and 35% polytrimethylene terephthalate are mixed, and a masterbatch is obtained by melt granulation; the masterbatch, 2% compatibilizer ABS-g-MAH and 56% polypropylene are mixed, and fibers are obtained by melt spinning; melt granulation parameters: temperature is 250°C, rotation speed is 140rpm; melt spinning parameters: temperature is 300°C, winding speed is 1200m / min;
[0043] Step 2: dissolving ethylenediamine in methanol to obtain a 50 wt% ethylenediamine solution; dissolving polyglutamic acid in deionized water to obtain a 5 g / mL polyglutamic acid solution; dissolving chitosan in acetic acid solution to obtain a 2 g / mL chitosan solution;
[0044] The fiber was immersed in a 50wt% ethylenediamine solution, stirred and reacted at 30°C for 80 minutes to obtain an amino fiber; the amino fiber was immersed in a polyglutamic acid solution, stirred and reacted at 30°C for 40 minutes, washed with deionized water after the reaction, and then immersed in a chitosan solution, stirred and reacted at 30°C for 40 minutes, and washed with acetic acid solution after the reaction; the above steps were repeated for the amino fiber 3 times to obtain a high-performance fiber.
[0045] Comparative Example 2: The preparation step of the double-layer coated ammonium polyphosphate material is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: By mass fraction, 2% carbon nanotube material and 35% polytrimethylene terephthalate are mixed, and master batches are obtained by melt granulation; the master batch, 2% compatibilizer ABS-g-MAH and 61% polypropylene are mixed, and fibers are obtained by melt spinning; melt granulation parameters: temperature is 250°C, rotation speed is 140rpm; melt spinning parameters: temperature is 300°C, winding speed is 1200m / min;
[0046] Step 2: dissolving ethylenediamine in methanol to obtain a 50 wt% ethylenediamine solution; dissolving polyglutamic acid in deionized water to obtain a 5 g / mL polyglutamic acid solution; dissolving chitosan in acetic acid solution to obtain a 2 g / mL chitosan solution;
[0047] The fiber was immersed in a 50wt% ethylenediamine solution, stirred and reacted at 30°C for 80 minutes to obtain an amino fiber; the amino fiber was immersed in a polyglutamic acid solution, stirred and reacted at 30°C for 40 minutes, washed with deionized water after the reaction, and then immersed in a chitosan solution, stirred and reacted at 30°C for 40 minutes, and washed with acetic acid solution after the reaction; the above steps were repeated for the amino fiber 3 times to obtain a high-performance fiber.
[0048] Comparative Example 3: Step 4 is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: The solvent is heated to 50°C, and then ammonium polyphosphate and alkylphenol polyoxyethylene ether are added and the pH is adjusted to 10. After stirring evenly, tetraethyl orthosilicate is slowly added, and the reaction is stirred at 50°C for 5 hours. After the reaction is completed, the silicon-coated ammonium polyphosphate material is prepared by cooling, filtering, washing and drying; the silicon-coated ammonium polyphosphate material is mixed with anhydrous ethanol, fully stirred for 40 minutes, and then the temperature is raised to 70°C and γ-aminopropyl triethoxysilane is added dropwise, and stirring is continued for 40 minutes. After the reaction is completed, the modified silicon-coated ammonium polyphosphate material is prepared by cooling, filtering, washing and drying; wherein the solvent is composed of anhydrous ethanol and deionized water in a volume ratio of 3:1; the reaction mass ratio of ammonium polyphosphate, alkylphenol polyoxyethylene ether, tetraethyl orthosilicate and γ-aminopropyl triethoxysilane is 10:0.1:2.5:1;
[0049] Step 2: adding tris(hydroxymethyl)aminomethane hydrochloride to obtain a buffer solution with a pH of 8.5; adding tannic acid and modified silicon-coated ammonium polyphosphate material to the buffer solution, stirring at 30° C. for 7 hours, and after the reaction is completed, filtering, washing, and drying to obtain a double-layer coated ammonium polyphosphate material; the reaction mass ratio of tannic acid to modified silicon-coated ammonium polyphosphate material is 1:1.2;
[0050] Step 3: In terms of mass fraction, 2% carbon nanotube material, 5% double-layer coated ammonium polyphosphate material and 35% polytrimethylene terephthalate are mixed, and a masterbatch is obtained by melt granulation; the masterbatch, 2% compatibilizer ABS-g-MAH and 56% polypropylene are mixed, and high-performance fibers are obtained by melt spinning; melt granulation parameters: temperature is 250°C, rotation speed is 140rpm; melt spinning parameters: temperature is 300°C, winding speed is 1200m / min.
[0051] Detection test:
[0052] Flame retardant performance test: The high-performance fiber prepared by the present invention is used as a sample, and the flame retardant performance of the sample is tested using a limiting oxygen index instrument according to standard FZ / T50016-2011 "Test method for flame retardant performance of viscose staple fibers - oxygen index method".
[0053] Antibacterial performance test: The high-performance fiber prepared by the present invention is used as a sample, and the antibacterial performance of the sample is tested according to standard FZ / T73023-2006, and the test strain is Staphylococcus aureus. The bacterial solution is cultured at 25°C for 30 hours, and then the cultured bacterial solution is inoculated on the sample, and shaken at 24°C for 20 hours to obtain a pre-treated bacterial solution; the pre-treated bacterial solution is then diluted and inoculated into an agar medium, and cultured at 25°C for 24 hours; finally, the antibacterial rate is calculated according to the formula. The results are as follows:
[0054] Oxygen index% Antibacterial rate% Example 1 28.6 97 Example 2 28.5 96 Example 3 28.4 95 Comparative Example 1 25.4 93 Comparative Example 2 21.3 92 Comparative Example 3 27.1 78
[0055] Conclusion: The dosage of Examples 1 to 3 remains unchanged, and only some reaction parameters are modified. From the experimental data, it can be seen that there is no obvious fluctuation in the performance of the samples.
[0056] Comparative Example 1: The double-layer coated ammonium polyphosphate material is replaced with ammonium polyphosphate provided by Shandong Hui'an Chemical Co., Ltd., and the rest is the same as Example 1. It can be seen from the experimental data that compared with Example 1, the oxygen index is reduced to 25.4%. The reasons are analyzed as follows: on the one hand, the flame retardancy of the fiber can be significantly improved by introducing a silicon layer and a dopamine-like layer on the surface of ammonium polyphosphate. On the other hand, the compatibility of the ammonium polyphosphate flame retardant material with other components can be improved by introducing a dopamine-like layer on the surface of ammonium polyphosphate, thereby further improving the flame retardancy of the fiber. Therefore, after replacing the double-layer coated ammonium polyphosphate material with ordinary ammonium polyphosphate, the oxygen index of the sample is reduced and the flame retardant performance is reduced.
[0057] Comparative Example 2: The preparation steps of the double-layer coated ammonium polyphosphate material are removed, and the rest are the same as Example 1. It can be seen from the experimental data that compared with Example 1, the oxygen index is reduced to 21.3%. The reason is analyzed as follows: the double-layer coated ammonium polyphosphate material prepared by the present invention has excellent flame retardant effect, so after removing it, the oxygen index of the sample is reduced and the flame retardant performance is reduced.
[0058] Comparative Example 3: Step 4 is removed, and the rest is the same as Example 1. It can be seen from the experimental data that compared with Example 1, the antibacterial rate is reduced to 78%. The reason is analyzed as follows: the present invention prepares an antibacterial layer on the fiber surface by electrostatic layer-by-layer self-assembly to obtain a high-performance fiber with excellent antibacterial properties. Therefore, after the antibacterial treatment in step 4 is removed, the antibacterial rate is reduced and the antibacterial performance is reduced.
[0059] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0060] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing high-performance fibers containing carbon nanotubes, characterized in that: The following steps are involved: Step 1: heating the solvent to 45-50°C, adding ammonium polyphosphate and alkylphenol polyoxyethylene ether and adjusting the pH to 9-10, stirring evenly, and then slowly adding tetraethyl orthosilicate, stirring and reacting at 45-50°C for 4-5h, cooling, filtering, washing and drying after the reaction to prepare a silicon-coated ammonium polyphosphate material; The silicon-coated ammonium polyphosphate material and anhydrous ethanol are mixed, stirred for 30-40 minutes, then the temperature is raised to 60-70°C and γ-aminopropyltriethoxysilane is added dropwise, and the stirring is continued for 30-40 minutes. After the reaction is completed, the modified silicon-coated ammonium polyphosphate material is prepared by cooling, filtering, washing and drying; Step 2: adding tris(hydroxymethyl)aminomethane hydrochloride to obtain a buffer solution with a pH of 8.3-8.5; adding tannic acid and modified silicon-coated ammonium polyphosphate material to the buffer solution, stirring at 25-30° C. for 5-7 hours, filtering, washing and drying after the reaction to obtain a double-layer coated ammonium polyphosphate material; mixing the carbon nanotube material, the double-layer coated ammonium polyphosphate material and poly(trimethylene terephthalate), and obtaining a masterbatch by melt granulation; mixing the masterbatch, compatibilizer ABS-g-MAH and polypropylene, and obtaining fibers by melt spinning; Step 3: Immerse the fiber in ethylenediamine solution, stir and react for 60-80 minutes to obtain amino fiber; immerse the amino fiber in polyglutamic acid solution, stir and react for 30-40 minutes, wash with deionized water after the reaction, immerse in chitosan solution, stir and react for 30-40 minutes, wash with acetic acid solution after the reaction; repeat the above steps for the amino fiber 3 times to obtain high-performance fiber.
2. The method for preparing a high-performance fiber containing carbon nanotubes according to claim 1, characterized in that: In step 1, the solvent consists of anhydrous ethanol and deionized water in a volume ratio of 3:(1.0-1.5).
3. The method for preparing a high-performance fiber containing carbon nanotubes according to claim 1, characterized in that: In step 1, the reaction mass ratio of ammonium polyphosphate, alkylphenol polyoxyethylene ether, tetraethyl orthosilicate and γ-aminopropyltriethoxysilane is 10:0.1:(2.0-2.5):
1.
4. The method for preparing a high-performance fiber containing carbon nanotubes according to claim 1, characterized in that: In step 2, the reaction mass ratio of tannic acid and modified silicon-coated ammonium polyphosphate material is 1: (1.0-1.2)。 5. The method for preparing high-performance fibers containing carbon nanotubes according to claim 1, characterized in that: In step 2, the contents of the fiber components are: by mass fraction, 2-5% carbon nanotube material, 5-8% double-layer coated ammonium polyphosphate material, 30-36% polytrimethylene terephthalate, 2-5% compatibilizer ABS-g-MAH, and the remainder is polypropylene.
6. The method for preparing high-performance fibers containing carbon nanotubes according to claim 1, characterized in that: In step 2, the melt granulation parameters are: temperature of 200-250° C. and rotation speed of 120-140 rpm.
7. The method for preparing high-performance fibers containing carbon nanotubes according to claim 1, characterized in that: In step 2, melt spinning parameters are: temperature of 250-300° C., winding speed of 1000-1200 m / min.
8. The method for preparing high-performance fibers containing carbon nanotubes according to claim 1, characterized in that: In step 3, the stirring reaction temperature is 25-30°C.
9. The method for preparing high-performance fibers containing carbon nanotubes according to claim 1, characterized in that: In step three, ethylenediamine is dissolved in methanol to obtain a 40-50wt% ethylenediamine solution; polyglutamic acid is dissolved in deionized water to obtain a 3-5g / mL polyglutamic acid solution; chitosan is dissolved in acetic acid solution to obtain a 1-2g / mL chitosan solution.
10. A high-performance fiber comprising carbon nanotubes, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
High-flow conductive polypropylene composite material and preparation method thereof
CN120005324A
Thermal insulation and waterproof integrated structural coiled material and preparation method thereof
CN121316369A